Analysis on the stress mechanism of the exposed steel anchor box composite cable–pylon anchorage structure. (15th April 2023) - Xu, Haijun; Liu, Yuqing; Lu, Chi
Abstract: For the exposed steel anchor box cable–pylon anchorage structure, there is a good application prospect in urban bridges of medium and small span due to its good mechanical behavior, easy construction and beautiful overall appearance. This paper reveals the stress-transfer mechanism of the exposed steel anchor box cable–pylon anchorage structure through a segmental model test with a scaled-down ratio of 1:2, and focused on the effect of prestress in the pylon. Three calculation modes for the anchorage structure are proposed, and simplified calculation equations of the horizontal load distribution relationship and the vertical shear force of the stud are derived. The effects of various design parameters on the load distribution ratio, the pylon wall tension caused by shrinkage and the vertical shear force of the studs are discussed by using the simplified calculation equation. The research results show that the exposed steel anchor box cable–pylon anchorage structure has good applicability in medium and small span bridges. Prestress can significantly reduce the tensile stress of the pylon wall concrete, and improve its crack resistance. There is no significant difference between the results of the simplified calculation equations and the finite element calculation, and the simplified calculation equations meet the design requirement. Highlights: The stress-transfer of exposed steel anchor box revealed by a segmental model test. Simplified calculations of horizontal load distribution and vertical shear force. Prestress reduces the tensile stress of the pylon wall and improves crack resistance. The design requirements can be satisfied by the simplified calculations.